PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur periode 2013-2015) - Deny Prasetyo; Totok Dewayanto (Diponegoro Journal of Accounting, 2019)
This research aims to examine the effects of the characteristics of the board of commissioners as measured by the number of board of commissioners, the proportion of independent commissioners, frequency of board of commissioners meetings, board of commissioners diversity, and the educational qualifications of board members as independent variables on the performance of companies in the manufacturing sector in Indonesia. The company's performance as a dependent variable is measured by ROA (Return on Assets).Researcher uses secondary data with a population of all manufacturing companies listed on the Indonesia Stock Exchange in the 2013-2015 period. The sampling method in this study was purposive sampling with certain criteria. After going through sampling and processing data, the final sample that is worth observing in the study is 204 companies. The analysis technique in this study uses multiple regression analysis.The results showed that the size of the board of commissioners and the diversity of the board of directors had a significant positive effect on company performance, while the frequency of board meetings had a significant negative effect on company performance, and the proportion of independent commissioners and education qualifications of the board of commissioners had no effect on company performance.